Comparing management actions in groundwater related wetlands that provide significant services to human welfare in Ibero-America (2016)
ABSTRACT: Wetlands are important features of the landscape with a high intrinsic value from geological, hydrological, hydrogeological, ecological and social points of view; this last point is related to the services they provide to mankind. If in the past wetlands were subjected to destructive actions, putting them at risk of degradation and further reduction, currently they are the subject of preferential protection in many countries as a consequence of the recognition of their intrinsic value. Wetlands are especially important in arid and semiarid areas, where many of them are related to, and depend greatly on, groundwater. Also, in wet areas groundwater may play an important role, especially providing resilience to rainfall changes. UNESCO’s International Geoscience Programme Project 604 (IGCP 604) has been directed to the consideration of selected wetlands of Ibero-America,the Iberian Peninsula and related archipelagos to relate their physical and water quality characteristics with the services they provide and the drivers of change. After preparing a detailed form based on the objectives of the project and distributing it to selected experts, a total of 64 cases from 13 countries have been gathered. The main characteristics, the services provided, the conservation institutions are discussed and some summarized results are given. These are expected to be a contribution to the systematics of IGCP type studies on wetlands and to establish a common methodology and language among Earth Science and Biological Science researchers and managers. Results indicate that deterioration of the condition of wetlands is mainly due to the lack of integration of protection activities with management. This is crucial for more effective conservation.